2020
DOI: 10.1016/j.lfs.2020.118207
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of COVID-19 in different biologic matrix, their diagnostic validity and clinical relevance: A systematic review

Abstract: Due to COVID 19 outbreak many studies are being conducted for therapeutic strategies and vaccines but detection methods play an important role in the containment of the disease. Hence, this systematic review aims to evaluate the effectiveness of the molecular detection techniques in COVID-19. For framing the systematic review 6 literature databases (PubMed, EMBASE, OVID, Web of Science, Scopus and Google Scholar) were searched for relevant studies and articles were screened for relevant content till 25th April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 74 publications
0
9
0
1
Order By: Relevance
“…Dust et al [ 16 ] reported the performance of different commercial SARS-CoV-2 RT-PCR assays testing clinical samples and reference material, ranging the sensitivity from 24 copies/mL to 574/mL specimen. However, the RT-PCR sensitivity, specificity, and positive or negative predictive values are still very difficult to determine without clear gold standard tests for SARS-COV-2 [ 17 ]. Previous studies have described positive RT-PCR in asymptomatic pregnant women rates ranging between 50% and 89% [ 8 , 9 , 11 , 12 ], our 66.7 % in our small sample seems to fit well within reported ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Dust et al [ 16 ] reported the performance of different commercial SARS-CoV-2 RT-PCR assays testing clinical samples and reference material, ranging the sensitivity from 24 copies/mL to 574/mL specimen. However, the RT-PCR sensitivity, specificity, and positive or negative predictive values are still very difficult to determine without clear gold standard tests for SARS-COV-2 [ 17 ]. Previous studies have described positive RT-PCR in asymptomatic pregnant women rates ranging between 50% and 89% [ 8 , 9 , 11 , 12 ], our 66.7 % in our small sample seems to fit well within reported ranges.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR-based molecular methods represent the gold standard techniques used worldwide to make a confirmatory diagnosis of COVID-19 infection ( 46 ). Since the complete sequencing of the SARS-CoV-2 genome ( 26 ), researchers of different countries have begun to design molecular primers and probes specific to SARS-CoV-2 RNA sequences in order to perform differential diagnosis between COVID-19 infections and other pathologies with similar symptoms, such as seasonal flu or bacterial infections ( 47 , 48 ).…”
Section: Rt-pcr-based Molecular Testsmentioning
confidence: 99%
“…Metoda detekcije, koja predstavlja zlatni standard za dijagnozu SARS-KoV-2 virusa je RT-PCR test iz nazofaringealnog brisa [42]. Do lažno negativnog nalaza RT-PCR testiranja na SARS-KoV-2 može doći zbog nedovoljne količine virusa, kada se uzorak prerano ili prekasno uzme u toku bolesti, kao i zbog tehničkih grešaka prilikom rukovanja ili slanja materijala.…”
Section: Clinical Presentationunclassified